ALTERATIONS IN REDOX HOMEOSTASIS IN ELITE ENDURANCE ATHLETES DIAGNOSED WITH UNEXPLAINED UNDER-PERFORMANCE SYNDROME (OVERTRAINING SYNDROME). Issue 4 (1st February 2017) - Lewis, Nathan; Rogers, John; Towey, Colin; Howatson, Glyn; Moore, Brian; Pedlar, Charlie
Abstract : Background: Alterations in redox homeostasis (ARH) have been implicated in the pathophysiology of Unexplained Under-Performance Syndrome (UUPS). No studies have investigated alterations in ARH in elite athletes with UUPS. Objective: To investigate concentrations of antioxidant nutrients and enzymes in world-class endurance athletes diagnosed with UUPS. Design: Prospective observational case-control study. Setting: UUPS was diagnosed by a sports medicine physician and referred to sports science and nutrition science practitioners for an exercise test, blood work, nutritional history, and an interview involving a questionnaire. Control athletes were required, not to have suffered with any fatigue associated training restrictions for the past four years (Olympic cycle); and tested in the competitive season to ensure performing successfully. Patients (or Participants): Elite endurance athletes from Track & Field and Triathlon (n=16, of which 9 were UUPS and 7 were controls). The athletes were competing at national and international standard, including World and European Championship, Commonwealth and Olympic Games medallists. Main Outcome Measurements: Redox biomarkers (α- and β-carotene, lutein, α- and γ-tocopherol, red blood cell superoxide dismutase, total glutathione, and co-enzyme Q10) were measured at rest. Results: Resting hydroperoxides (FORT) were significantly higher in controls vs. UUPS athletes (1.40±0.12 vs. 1.89±0.20 mmolŸL −1 H2 O2 ; p<0.001, g =2.87). Controls had higher concentrations of total carotenoids (1.49±.052 µmolL −1 vs. 3.16±1.07 µmolL −1, p=0.006, g=2.07) and α-tocopherol than UUPS athletes (22.78±8.54 µmolL −1 vs. 31.71±5.80 µmolL −1, p=0.039, g =1.19). No between-group differences were identified for RBC GSH, SOD, co-enzyme Q10 and γ-tocopherol. Conclusions: UUPS athletes have lower concentrations of antioxidant nutrients than healthy elite athletes. We speculate that the measurement of antioxidant nutrients and subsequent dietary interventions may reduce the risk of UUPS in elite endurance athletes.